Pemilihan Karir Sebagai Akuntan Publik Bagi Mahasiswa Perguruan Tinggi Swasta Dengan Pendekatan Theory Of Planned Behaviour - Hendro Lukman; Sugim Winata (Jurnal Akuntansi, 2017)
The purpose of this study is tosee how the attitude,subjectnorms, perceivedbehavior control and intention to behavior for a career as a public accountant in theperception of accounting students at private universities in Jakarta by using the approachof The Theory of Planned Behaviour (TPB). Data collected for processedweretotal of106 questionnaires. Data processed by using Stata, showed that attitude, subject norms andperceived behavior control has a weak correlationand no significant effect amongthosevariables,on student intention became public accountants,andto the behavior of a careeras a public accountant through intention as mediating variable. However, the relationshipbetween intentionon student becomea public accountant to the behavior of a career as apublic accountant has a strong relationship and have a significant impact. It can beconcluded that the respondents' interest in working as a public accountant only temporarilyas a stepping stone to other professions.